SMG311 - Leadership in Sports and Recreation / Faculty of Sports Science & Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2024)
This course will provide students with opportunity to learn about leadership and methods of leading recreation activities. The course will focus on theory, technique, and application of personal leadership skills in recreation setting. Student will be presented with leadership styles, characteristics, and practices including group dynamics and leadership method.